Pengaruh Simplifikasi Alur dan Berkas Layanan Administrasi Kepesertaan Terhadap Kepuasan Peserta JKN di Kantor BPJS Kesehatan Cabang Kupang - Bau, Ariasto; Kapitan, Gregorius D. (Jurnal Jaminan Kesehatan Nasional, 2024)
The Social Insurance Administration Body for Health (BPJS Health), the institution administering national health insurance in Indonesia, has an important role in ensuring people have access to quality health services. The method taken by The Social Insurance Administration Body for Health to minimize complaints and reduce waiting times for services is by simplifying administrative service flows and files. This research design is quantitative and descriptive to describe the effect of simplifying participant service flows and files at branch offices on the satisfaction of the National Health Insurance participants at the Kupang Branch Office. The research sample consisted of 50 people using the Simple Random Sampling technique. Research data analysis was carried out univariately. The research results show that a simple flow and file of service requirements will make it easier for the National Health Insurance participants to obtain administrative services and simplifying services for participants will have an impact on achieving participant satisfaction with services at the Social Insurance Administration Body for Health office. The Social Insurance Administration Body for Health is expected to pay attention to the satisfaction of the National Health Insurance participants by committing to implementing simplification of service flows and processes to achieve good service quality.